- The Influence of Locus of Control, Academic Ability, and Financial Attude on Student Financial Management Behavior: Locus of Control, Academic Ability, Financial Attitude, Student's Fiinancial Management Behavior - Sisya Citrawati; Sih Mirmaning Damar Endah (Jurnal Proaksi, 2025)
Main Purpose – This study aims to examine the factors that influence students' financial management behavior. Some of the research factors included in the study are locus of control, academic ability and financial attitude. Method – The research uses a quantitative approach and the data is processed using statistical analysis methods. The research sample amounted to 80 accounting student respondents in Semarang's A accredited private universities using purposive sampling technique. Main Findings – The results showed that locus of control, academic ability and financial attitude have a significant effect on student financial management behavior. Theory and Practical Implications – This study can provide in-depth knowledge in managing effective finances for accounting students who have a business. The results of the study can also be a reference for educational institutions in improving financial literacy through comprehensive educational programs. Novelty – This research has a novelty by including the academic ability factor as one of the things analyzed in seeing how students who own businesses, especially accounting students, manage their finances.